2013
DOI: 10.1016/j.scitotenv.2013.02.070
|View full text |Cite
|
Sign up to set email alerts
|

Indoor air quality of a museum in a subtropical climate: The Oscar Niemeyer museum in Curitiba, Brazil

Abstract: The assessment of damage to indoor cultural heritage, in particular by pollutants, is nowadays a major and growing concern for curators and conservators. Nevertheless, although many museums have been widely investigated in Europe, the effects of particulate matter and gaseous pollutants in museums under tropical and subtropical climates and with different economic realities are still unclear. An important portion of the world's cultural heritage is currently in tropical countries where both human and financial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…It was found that the model failed to generate several peaks of indoor particle concentration. Although, the indoor concentration of coarse particles at the size interval 3-20 µm was negligible in all three seasons, it was assumed that this [7][8][9]26,49]. Thus, in order to determine appropriate values of k and P for coarse particles, the indoor concentration was compared in parallel with the outdoor.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that the model failed to generate several peaks of indoor particle concentration. Although, the indoor concentration of coarse particles at the size interval 3-20 µm was negligible in all three seasons, it was assumed that this [7][8][9]26,49]. Thus, in order to determine appropriate values of k and P for coarse particles, the indoor concentration was compared in parallel with the outdoor.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Indoor pollutants in cultural heritage buildings may originate either from indoor sources or penetrate indoors through the building envelope [4,[7][8][9]. Common indoor sources include heating, smoking, cleaning or walking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the opposite, a high value of the humidity favor mold development (Anaf et al, 2013;Janssen and Christensen, 2013) and could represent a favorable environment that accelerate the degradation of artifacts. Moreover, the destructive effect could be accelerated by the high concentrations of gaseous compounds from indoor air (Godoi et al, 2013;Saraga et al, 2011); for example, the sulfur and nitrogen oxides could directly react with materials of the artifacts, damaging them. This harmful effect could be amplified in the presence of humidity (Kontozova-Deutsch et al, 2011) and metal cations-catalysts of oxide transformation, in strong and corrosive acids (Loupa et al, 2007;Kontozova-Deutsch et al, 2011;Chianese et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Diffusive sampling can overcome these problems since it represents an easy to use technique which exploits the spontaneous diffusion of species collected by specific absorbing media. Diffusive samplers have been used for air quality monitoring of single gases in cultural Open Access *Correspondence: maskova@icpf.cas.cz 2 Institute of Chemical Process Fundamentals of the CAS, Rozvojová 135, 165 02 Prague, Czech Republic Full list of author information is available at the end of the article heritage buildings [20][21][22][23]. Nevertheless, when conditions which promote the formation of HONO are present (high air moisture content and surface to volume ratio), especially indoors, monitoring of NO 2 by diffusive sampling can result in overestimation since the interference of the former pollutant is not negligible [24].…”
Section: Introductionmentioning
confidence: 99%